Facial danger zones avoiding nerve injury in facial plastic surgery - Seckel, Brooke R.
Subperiosteal, extended sub-SMAS, deep plane, and composite rhytidectomy are all names that have been used to describe the current, more extensive operations for facial rejuvenation. Although these procedures provide superior results, they also involve deeper dissections with the potential for injury to the facial nerves. In order to avoid injury to these nerves, a thorough understanding of their locations is crucial for surgeons performing these operations.